Analysis of Prognostic Factors of Bell’s Palsy in a Tertiary Care Centre of Eastern Nepal - Paudel, D.; Chettri, S. T.; Sah, B. P.; Dahal, R.; Pyakurel, P. (Kathmandu University Medical Journal, 2021)
Background Bell’s palsy is the most common cause of acute facial peripheral neuropathy commonly encountered in otolaryngology clinics. Studies regarding epidemiology, risk factors, treatment and prognosis of Bell’s palsy are sparse in our settings. Objective To analyze the prognostic factors of Bell’s palsy in tertiary care Centre of eastern Nepal. Method A retrospective chart review of patients diagnosed with Bell’s palsy from 1st January 2005 to 31st December 2018 was done. Records of the patients were obtained from medical record section of BP Koirala Institute of Health Sciences. Result A Total of 208 patients were included for analysis. After six months 72.6% patients had complete recovery. Patients who presented with lower House Brackmann (HB) grade had significantly better complete recovery than those with high grade (89.1% vs 45.6%). The complete recovery was 80.3%, 73.8%, 63.5% and 50% for the patients of more than 30 yrs, 31-45 years, 46-60 years and more than 60 years respectively and the difference was significant (p= 0.012). Alcohol significantly reduced the complete recovery (p= 0.043). Multivariate analysis showed high HB grade score at presentation to be significant predictor of poor prognosis. (p= 0.001 odds ratio 11.262). Conclusion Old age, use of alcohol and the severity of facial nerve palsy at the time of presentation were the bad prognostic factors, severity of the palsy was found to be most significant predictor.